Cultural Adaptation of A Respite Program For Caregivers Of Mentally Challenged Children In Pakistan: A Qualitative Study - Saman Waqar; Hayaa Ali; Imran Marwat; Eeman Ali; Ayesha Babar (Kurdish Studies, 2024)
In low-income countries like Pakistan, caring for children with special needs is challenging due to a shortage of mental health providers. This study adopted a Respite Program from a developed country to support caregivers of mentally challenged children. Thirty interviews with caregivers and family volunteers at a rehabilitation institute led to training manual adjustments. The 5-session intervention was found convenient and acceptable, with high satisfaction reported. Most participants wanted extended intervention and volunteer training in daily living activities. Three main themes emerged: The perspective of the participants on the intervention, The listening skills exercises in the facility, and, Input on the intervention manual for home practice. Culturally adapted interventions benefit caregivers and children, fostering trust and accessibility across diverse backgrounds.